Macroeconomic Effects of Financial Shocks - Jermann, Urban; Quadrini, Vincenzo (American Economic Review, 2012)
We document the cyclical properties of US firms' financial flows and show that equity payout is procyclical and debt payout is countercyclical. We then develop a model with debt and equity financing to explore how the dynamics of real and financial variables are affected by “financial shocks.” We find that financial shocks contributed significantly to the observed dynamics of real and financial variables. The recent events in the financial sector show up as a tightening of firms' financing conditions which contributed to the 2008–2009 recession. The downturns in 1990–1991 and 2001 were also influenced by changes in credit conditions. (JEL E23, E32, E44, G01, G32)